Analysis of Self-Efficacy, Creativity, and Relationship with Implementation Learning Innovation of Senior High School Teachers in Malang City - Azizatunnisa, Azizatunnisa; Sunandar, Asep; Sobri, Ahmad Yusuf (Proceedings Series of Educational Studies, 2024)
The aims of research are: (1) knowing teacher self-efficacy; (2) knowing teacher creativity; (3) knowing the application of teacher learning innovations; (4) knowing the relationship between teacher self-efficacy and the application of teacher learning innovations; (5) knowing the relationship between creativity and the application of teacher learning innovations; (6) knowing the relationship between self-effiacy and creativity with the application of teacher learning innovations in public high schools in Malang City. The research used a quantitative approach with a descriptive correlational research design. Sampling technique using propotional random sampling technique was used for each school with a total sample size of 167 certified teachers (Civil Servants). The analysis techniques used are descriptive analysis techniques, prerequisite analysis tests, and hypothesis testing with the help of IBM SPSS Statistic 20. The results of the study are (1) the self-efficacy variable is in the very high category; (2) the creativity variable is in the high category; (3) the variable application of teacher learning innovation is in the high category; (4) there is a positive and significant relationship between self-efficacy and the application of teacher learning innovation; (5) there is a positive and significant relationship between creativity and the application of teacher learning innovation; and (6) there is a positive and significant relationship between self-efficacy and creativity with the application of teacher learning innovation in public high schools in Malang City. Keywords: relationship; self-efficacy; creativity; implementation of learning innovations; teacher